2020
DOI: 10.51441/biomedica//biomedica/5-414
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Health Care Workers during COVID-19

Abstract: <p><strong>Background and Objective: </strong>Pakistan has been sternly affected by COVID-19 (Coronavirus Disease 2019) since March, 2020. This study was intended to evaluate the mental health among health care workers throughout the epidemic and to sight see the possible influence factors. <strong>Methods: </strong>A web-based cross-sectional survey composed of n = 237 self-selected health care workers was conducted. Their demographics, COVID-19 associated knowledge, Hospital Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Content may be shared at no cost, but any requests to reuse this content in part or whole must go through the American Psychological Association. A critical finding of the present study is that the COVID-19 pandemic represents a unique situation in which employed young racial/minority adults face greater risk for depression and anxiety (McKnight-Eily et al, 2021;Mehdi et al, 2020). Our data suggest this is not only due to the infection risks associated with work outside the home during the pandemic, but also due to increased engagement in cross-race interactions that increased exposure to victimization and racial bias, based in part on social perceptions that racial minorities were more likely to be infected with the virus (Goldman et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Content may be shared at no cost, but any requests to reuse this content in part or whole must go through the American Psychological Association. A critical finding of the present study is that the COVID-19 pandemic represents a unique situation in which employed young racial/minority adults face greater risk for depression and anxiety (McKnight-Eily et al, 2021;Mehdi et al, 2020). Our data suggest this is not only due to the infection risks associated with work outside the home during the pandemic, but also due to increased engagement in cross-race interactions that increased exposure to victimization and racial bias, based in part on social perceptions that racial minorities were more likely to be infected with the virus (Goldman et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…These findings have been attributed to the fact that racial minorities in the U.S. seek mental health clinical care at rates well below their need, face discrimination during diagnosis and treatment, suffer from misdiagnosis and clinician bias, and within their communities mental health may be shrouded by silence and shame (Baldwin et al, 2020; Harkness et al, 2020; Mental Heath America, 2021; Novacek et al, 2020; Vilsaint et al, 2019). Further, although prior research has repeatedly reported on the protective effect of employment on mental health (McGee & Thompson, 2015; Paul & Moser, 2009), during the pandemic, employed individuals, especially those whose work involves in-person contact, are experiencing higher levels of depression and anxiety (McKnight-Eily et al, 2021; Mehdi et al, 2020). In 2020, people under the age of 30 accounted for more than 20% of COVID-19 cases, with young Black, Latinx young adults at greater risk than their counterparts; due in part to their disproportionate employment in health care, food, and essential services (Leidman et al, 2021).…”
Section: Racial Discrimination and Mental Healthmentioning
confidence: 99%
“…(2012) tarafından yapılmış olup, faktör analizleri ölçeğin 5 faktörden oluştuğunu göstermiştir. 19 23 Ülkemizde hemşirelerin çalışma koşullarına yönelik yaşadıkları sorunlar nedeniyle kaygı ve depresyon düzeyleri yükselmiş ve psikososyal risklerle karşı karşıya kalmışlardır. 24 Bu durum pandemi sürecinde çalışan hemşirelerin personel yetersizliği nedeniyle izinsiz çalışmaları, uzun çalışma saatleri, yetersiz dinlenme süreleri ve çalışma arkadaşlarının aniden COVID-19 tanısı almaları nedeni ile fazla mesaiye kalma gibi zor çalışma koşullarından kaynaklanmış olabilir.…”
Section: Veri Toplama Araçları Ve Süreçleriunclassified
“…Because of their work environment and subsequent potential exposure to COVID-19, healthcare workers present a high prevalence of early onset mental health disorders with mainly depressive and anxious symptoms [12][13][14][15][16][17][18]. Risk of transmission to family members was reported to be one of the caregivers' major concerns [16,19].…”
Section: Introductionmentioning
confidence: 99%